104k views
1 vote
identify all expressions equivalent to the given expressions. 2/3 • 9 ÷ 3 - 1 ANWSER: 6 ÷ 2 - 1 + 2 3 • 2/3 -12/3 • 9 ÷ 1

1 Answer

4 votes

Simplify each expression and find if the simplified form is the same.


2/3\cdot9/3-1

This can also be writen as:


=(2)/(3)\cdot9/3-1

Multiply 2/3 by 9:


=6/3-1

divide 6 by 3:


=2-1

Substract 1 from 2:


=1

Now, check each option:

6 ÷ 2

Divide both numbers:


(6)/(2)=3

This is NOT equivalent to the given expression.

- 1 + 2

Add the numbers:


-1+2=1

This IS equivalent to the given expression.

3 • 2/3 -1

First, multiply 3 times 2/3:


3\cdot(2)/(3)-1=2-1

Then, add both numbers:


2-1=1

This IS equivalent to the given expression.

2/3 • 9 ÷ 1​

Perform the operations from left to right:


\begin{gathered} (2)/(3)\cdot9/1=6/1 \\ =6 \end{gathered}

This is NOT equivalent to the given expression.

Therefore, the expressions that are equivalent to the given one, are:


\begin{gathered} -1+2 \\ 3\cdot2/3-1 \end{gathered}

User Luiz Alves
by
5.1k points